2013
DOI: 10.1007/s00595-012-0484-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid cysts of the lung: lesion size in relation to clinical presentation and therapeutic approach

Abstract: All pulmonary hydatid cysts should be surgically treated as soon as possible after their diagnosis in order to avoid complications. Most of these lesions, regardless of size, can be surgically managed with procedures that preserve the maximal lung parenchyma and yield excellent outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
2
35
2
4
Order By: Relevance
“…It is reported in literature that chest pain, cough, and dyspnea are the most common clinical symptoms of patients presenting with a pulmonary hydatid cyst; however, our patient developed only dyspnea regarding the fact that the size of the hydatid cyst was huge [4,8]. Kuzucu et al reported that patients having a hydatid cyst greater than 10 cm may present with productive cough and dyspnea more frequent than those having smaller pulmonary hydatid cysts [8].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is reported in literature that chest pain, cough, and dyspnea are the most common clinical symptoms of patients presenting with a pulmonary hydatid cyst; however, our patient developed only dyspnea regarding the fact that the size of the hydatid cyst was huge [4,8]. Kuzucu et al reported that patients having a hydatid cyst greater than 10 cm may present with productive cough and dyspnea more frequent than those having smaller pulmonary hydatid cysts [8].…”
Section: Discussionmentioning
confidence: 65%
“…There is no generally accepted size to define the diameter of the cyst as "huge," although in most studies, cysts more than 10 centimeters were regarded as "giant" or "huge" cysts [8]. In cases with huge hydatid cyst (more than 10 cm in diameter), postoperative complications are more frequent.…”
Section: Discussionmentioning
confidence: 99%
“…New surgical options include enucleation, wedge resection, segmentectomy, lobectomy and pulmonectomy, according to the location of lesion in the pulmonary parenchyma,15 with minimal visceral and parietal destruction 16. It is suggested that after diagnosis of the lesion, cysts should be surgically treated as soon as possible, preserving the maximum lung parenchyma regardless of their sizes 17. After surgery, a long follow-up is needed for recurrence and early treatment; our patient showed no signs of recurrence radiologically.…”
Section: Discussionmentioning
confidence: 73%
“…Los síntomas dependen del tamaño y localización del quiste. Se ha descrito dolor torácico en 56,6-69%, disnea en 37,3-47%, tos seca en 24,3-56%, expectoración hemoptóica en 8,9-43,5% y evacuación del contenido quístico en 4,7-11,5% (3,12,13), siendo esta última considerada una complicación. En un estudio se vio que la ruptura del quiste puede complicarse con hemoptisis franca, neumonía y neumotórax principalmente (13).…”
Section: Discussionunclassified